PERBAIKAN TATA LETAK GUDANG DENGAN MENGGUNAKAN METODE SHARED STORAGE PADA PERUM BULOG SUBDIVRE KARAWANG - Arifin, Jauhari; Pamungkas, Tri (Jurnal Media Teknik dan Sistem Industri, 2019)
Abstract--- Perum Bulog is a general company of state-owned enterprises in the field of logistics which has a role in maintaining national food availability and security such as prices for government purchases, distribution of rice and management of state-owned rice reserves. To maintain availability, products are stored and placed in a warehouse according to their needs and capacities by calculating how long it takes to store and deliver products to be marketed according to consumer demand. In the Bulog Karawang warehouse activity, there are still problems with poor product placement because irregular distances between the placement and shipping areas are caused by inappropriate product storage flow patterns so that loading and unloading activities become ineffective. Based on the existing problems, layout improvement design is carried out using shared storage methods in order to increase the effectiveness of the distance between the doors to the storage area. The steps to redesign using shared storage begin with knowing the warehouse area, warehouse capacity and other warehouse data, as well as collecting data by determining space requirements, determining space allowances, and distance from the entrance to the storage area by using Euclidean Distance. From the results of distance data processing becomes regular and can be known every distance. Based on the comparison of the initial layout and the proposal it is known that by implementing shared storage loading and unloading activities become better and more effective.                                                                             Keywords ; Allowance, Euclidean Distance, First In First Out (FIFO), Shared StorageAbstrak--- Perum Bulog adalah perusahaan umum badan usaha milik negara di bidang logistik yang memiliki peran dalam menjaga ketersediaan dan ketahanan pangan nasional seperti harga pembelian pemerintah, penyaluran beras dan pengelolaan cadangan beras milik negara. Untuk menjaga ketersediaan, produk disimpan dan diletakan pada suatu gudang sesuai kebutuhan dan kapasitasnya dengan menghitung waktu berapa lama simpan dan pengiriman produk yang akan dipasarkan sesuai permintaan konsumen. Pada aktifitas gudang Bulog Karawang masih mengalami permasalahan penempatan produk yang kurang baik karena tidak teraturnya jarak antar area penempatan dan pengiriman disebabkan tidak sesuai pola aliran penyimpanan produk sehingga aktifitas bongkar muat menjadi tidak efektif. Berdasarkan permasalahan yang ada, dalam penelitian ini, dilakukan perancangan perbaikan tata letak menggunakan metode shared storage dengan tujuan dapat meningkatkan efektifitas jarak antar pintu ke area penyimpanan. Langkah-langkah perancangan ulang menggunakan shared storage dimulai dengan mengetahui luas area gudang, kapasitas gudang dan data gudang lainnya, serta pengumpulan data dengan menentukan kebutuhan ruang, penentuan allowance ruang, dan jarak dari pintu masuk ke area penyimpanan dengan menggunakan Euclidean Distance. Dari hasil pengolahan data jarak menjadi teratur dan dapat diketahui tiap jaraknya. Berdasarkan perbandingan layout awal dan usulan diketahui dengan menerapkan shared storage aktifitas bongkar muat menjadi lebih baik dan efektif.Kata kunci ; Allowance, Euclidean Distance, First In First Out (FIFO), Shared Storage.